TATO and ROA Influence on Stock Returns: Evidence from the Jakarta Islamic Index - Oktasaputra, Wahyu (Islamicate Institute, 2019)
This study examines how Total Asset Turnover (TATO) and Return on Assets (ROA) influence stock returns in companies listed on the Jakarta Islamic Index (JII). Within Islamic capital markets, conventional financial ratios are used cautiously, as they must align with Shariah principles. Using a qualitative and conceptual method, the study reviews relevant academic, regulatory, and doctrinal sources to assess the role of these indicators in a Sharia-compliant context. Findings show that ROA consistently correlates positively with stock performance, indicating its robustness as a profitability measure within Islamic frameworks. TATO, by contrast, shows a more variable influence, dependent on industry and asset deployment. The study proposes that these financial indicators must be interpreted through ethical filters to reflect compliance and value-based performance. Implications include the need for Islamic-adjusted financial metrics and enhanced investor education to ensure both profitability and religious conformity in stock evaluation.